2017
DOI: 10.1016/j.nurpra.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Care in the Elderly

Abstract: Type 2 diabetes mellitus is a major chronic disease worldwide. Over the next decade, the largest increase in diabetes prevalence is expected to be in those > 75 years old. Diabetes self-care and prevention of complications can be challenging, but, when combined with the demands of self-care for other chronic conditions, it can become overwhelming to patients and caregivers. The glycemic targets and treatment options are unique to older adults. Clinicians should treat elderly patients with diabetes based on com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…In addition, the demand of insulin may increase in the human body in certain context or improper utilization of insulin by the body among aged people 42,43 . The suggestive actions for older adults were maintaining blood pressure, blood sugar through improving lifestyle [44][45][46][47][48][49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the demand of insulin may increase in the human body in certain context or improper utilization of insulin by the body among aged people 42,43 . The suggestive actions for older adults were maintaining blood pressure, blood sugar through improving lifestyle [44][45][46][47][48][49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
“…These studies have identified risk factors for TB in the elderly, including aging itself, male sex, smoking, and malnutrition, undernutrition or low body mass index (BMI) [11]. Although diabetes increases the risk of TB by 3-fold among adults [13], the link between TB and diabetes in the elderly has not been formally studied. Instead, association studies among all adults suggest a stronger link to diabetes among middle-aged vs. older adults (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary principles are the pillars of nonpharmacological treatment of type 2 diabetes mellitus. However, older adults have formed lifetime habits that may be difficult to change [13].…”
Section: Discussionmentioning
confidence: 99%